Studies on Mineral Supplementation in the Swamp Buffalo - Pratas, Rachjan Gunasah (1983)
Two experiments were conducted to study (a) the effect of mineral supplements on weight gain and on blood plasma calcium, inorganic phosphorus, magnesium, iron and copper in male and female swamp buffalo calves up to 10 months of age and (b) the effects of mineral and energy supplementation on the utilization of Guinea grass by swamp buffaloes. In the first experiment, 20 swamp buffalo calves (10 males, 10 females) were distributed into mineral supplemented and unsupplemented groups and rotationaly grazed through several paddocks and pasture species. Pastures comprised of Guinea (Panicum maximum), Signal (Brachiaria decumbens), Setaria (Setariaancep) and Star (Cynodon plectostachyus). Mineral supplementation with Phos-Rich, Rockies (Tithebarn, Ltd., England) had no significant effect on average daily gain from birth to weaning (6 months of age) and from birth to 10 months of age. However, mineral supplements had a significant (P<O.01) effect on average daily gain from weaning to 10 months of age. This experiment also demonstrated that there was a tendency for plasma inorganic phosphorus levels to be higher in supplemented animals as compared to unsupplemented animals. The concentration of plasma calcium had a tendency to be lower in the supplemented calves. Plasma inorganic phosphorus was negatively correlated (P<O.01) with age in both males and females. Plasma calcium levels in supplemented calves were positively correlated (P<O.O1) with age at 6 to 10 months of age but not significant at 2 to 6 months of age. In unsupplemented calves there were positive correlations (P<O.OI) with age (2 to 6 months) which were however not significant at 6 to 10 months of age. Average daily gain from birth to weaning (6 months of age) ranged from O.468-0.615 kg. Further, average daily gain from weaning to 10 months of age ranged from 0.527-0.537 kg for supplemented calves and 0.350-0.370 kg for unsupplemented calves. Plasma inorganic phospharus levels ranged from 8.26-9.19 mg per 100 ml (2 months), 4.68- 7.90 mg per 100 ml (6 months) and 3.84-4.43 mg per 100 ml at 10 months of age. Plasma calcium levels ranged from 5.04-6.69 mg per 100 ml (2 months), 7.21-8.29 mg per 100 ml (6 months ) and 10.02 to 11.08 mg per 100 ml at 10 months of age. Plasma magnesium levels of Swamp buffalo calves ranged from 1.03-3.85 mg per 100 ml while plasma iron and copper levels ranged from 1.33-1.76 mg per ml and from 0.43-1.19)mg per ml respectively.